PENGARUH AUDIT LAG, REPUTASI AUDITOR, LIKUIDITAS, DAN OPINION SHOPPING TERHADAP OPINI AUDIT GOING CONCERN - Audia Vaneza Tria, (2020)
This research is using quantitative study aimed to test the effect of audit lag is measured with method of the number of days required to obtain an independent auditor's report from the closing date of the book to the time stated in the independent auditor's report. Auditor reputation measured the public accounting firm of big four and public accounting firm non-big four, liquidity measured by using current ratio, and opinion shopping as measured by the change of auditor every period of going concern audit opinion. The population used in this study are a real estate and property company listed in the Indonesia Stock Exchange in 2016-2018. The sample in this study amounted to 35 real estate and property companies found on the Indonesia Stock Exchange and the website of each company for the period 2016-2018 which were selected using the purposive sampling method. Hypothesis testing in this study was used Logistik Regression Analysis using SPSS analysis tool with a significant level of 5%. The result of hypothesis testing showed that (1) audit lag had positive significant effect on going concern audit opinion (2) auditor reputation does not have a significant effect on going concern audit opinion (3) liquidity had no significant effect on going concern audit opinion (4) opinion shopping does not significantly effect on going concern audit opinion.